Formação sócio-histórica de um novo ser social em tempos de acumulação flexível - Gilberto Braga Pereira (2012)
The present research connects the categories Generations-Work-Personality though an interpretation developed in the light of Marxian ontology of the social being, based mainly on sociohistorical psychology and on Lucien Sève´s (1979) concrete psychology. The theoretical corpus by which this research is directed can be specifically characterized as Marxist or historical materialist as regards the Marxian lineaments of the ontology of the social being and the development of individuality in an strict, ontological, and interchangeable relation with sociability. Our starting point were the theses of Sennet, R. (1999a), which preconize the corruption of character under the new capitalism, suggesting that what can be observed in flexible accumulation is the self-construction of historically circumscript personalities. Taking the social-dialectical category generations, the cohort phenomenon, and the category work as mediating activities in human self-construction, we have tried to make progress towards the elucidation of the individuation process, understanding it as historical, as well as of the self-formation of a new social being, that is, of a personality as the expression of the singularity of a contemporary individual. The object of analysis, even more than the corruption of character, is therefore the formation of a new social being in the era of flexible accumulation. As a methodological resource, we have adopted the biographic method with an emphasis on thematic oral history and on the professional journey of the individuals. Furthermore, we have utilized as research resources the author´s own files, made over course of his experience in consulting for several business organizations. The results allows for an advancement towards understanding that individuation, or personalization, consists in mediated self-construction wherewith work can be perceived as a foundational category, central to the dialectical relation between social being and the category generations. The study of the singular and the universal in the generative perspective made possible the observation of antagonisms, changes in values, senses, and significations in the relation between the generational cohorts and work and authority, in addition to dilemmas which point to questions pertaining to the social formation of the personality. The study has likewise contributed to making explicit that four selected cohorts are coetaneous whit the flexible reality of current capitalism and suffer or have suffered its impact, thereby confirming what Sennett (1999a) has been demonstrating for some years. But it compares and augments such findings with empirical records of national reality, permitting us to situate the cleavage (authoritarianism/flexible accumulation) observed from 1970s onwards in Brazil.